LINEAR FEATURE EXTRACTION FROM FORMOSAT-2 IMAGE FOR TOPOGRAPHIC MAP UPDATE - Wijanarto, Antonius B; Rahadian, Yusuf (GEOMATIKA, 2010)
Aerial or satellite remote sensing is rapidly being applied to map updating, and in other regions, most map series have been partly or fully digitized. It is important to update maps because nowadays, many countries face problems in relation to outdated topographic maps. In this paper FORMOSAT-2 images used as reference. This is based on the consideration that the image of FORMOSAT-2 has a high resolution, so that is expected to provide more accurate information than the previous RBI map. The aim of this work is to extract linear features such as road and river from FORMOSAT-2 image for topographic map updating.Keywords:Â Topographic Map, Map Update, FORMOSAT-2 Image.ABSTRAKPenginderaan jauh maupun foto udara telah diaplikasikan dengan cepat untuk pemuktahiran peta, dan di daerah lain kebanyakan peta-peta serial sebagian atau secara menyeluruh digitasi. Penting untuk memuktahirkan peta karena akhr-akhir ini banyak negara menghadapi maslah terutama dengan pemuktahiran peta topografi. Makalah ini membahas citra FORMOSAT-2 yang mempunyai resolusi tinggi, yang diharapkan dapat menyediakan informasi yang lebih akurat dari pada peta topografi sebelumnya. Tujuan dari kegiatan penelitian ini adalah mengekstrak fitur linear seperti jalan dan sungai dari citra FORMOSAT-2 untuk pemuktahiran peta topografi.Kata kunci: Peta topografi, pemuktahiran peta, FORMOSAT-2